To sustainable competitiveness: Bulgaria in the European context - Hadjitchoneva, Juliana (Leadership, Society, Strategic Visions, 2021)
This article discusses the competitiveness beyond its economic nature, infl uenced by the concept of sustainable development, and expanded to the issues of environmental in the centre, it is a crucial objective for the economies, reinforced by the common European challenges and context of development. In this sense, the study‘s purpose is to analyse the development of Bulgaria through several key factors of infl uence in the three directions. Based on them, specifi c recommendations are proposed to achieve sustainable competitiveness primarily through the achievement of high added value by stimulating intellectual capacity and increasing management effi ciency. Further, it is open a discussion about a new stage in the development of the competitive race, marked by „shared“ (cooperative, solidarity) competitiveness.